Real time analysis of volatile organic compounds (VOCs) in centenarians - Mazzatenta, Andrea; Pokorski, Mieczyslaw; Di Giulio, Camillo (Respiratory physiology & neurobiology, 2015)
•Centenarian as a model of human longevity and physiological process of aging.•Real time VOC analysis is a new physiological biomarker of respiratory system disorders.•Real time VOC profile and VOC fingerprint of centenarians are presented. Centenarians are a model to study human longevity and the physiological process of aging. A plethora of studies on this model show the complexity of the system. Laboratory studies fail to find a biomarker of senescence. The real time exhaled breath volatile organic compounds (VOCs) has been suggested as a new biomarker to detect and monitor physiological processes in the respiratory system. VOCs exhaled by centenarians have not been studied in the general population and across-age-groups. In the present study we investigated, in real time, the breath properties and VOC exhaled content in healthy centenarians as compared with non-centenarian seniors and young healthy subjects. We found distinctly different breath pattern and distribution profiles of VOCs in the centenarians. Thus, the VOCs measurement allowed to discriminate the differences between the age-groups. We propose a VOCs fingerprint as a biomarker underlying the physiological mechanisms of aging and longevity. Longevity should be considered physiologically as a new phase of life, characteristic of the well adapted subject.